2021
DOI: 10.1111/jocs.15504
|View full text |Cite
|
Sign up to set email alerts
|

Total thoracoscopic repair of ventricular septal defect: A single‐center experience

Abstract: Objectives: To explore the safety and efficacy of total thoracoscopic repair of ventricular septal defects (VSD). We compared clinical outcomes of VSD via a total thoracoscopic approach with those of mini-sternotomy. Methods:We retrospectively reviewed clinical data from patients with VSD from 2012 to January 2019. According to the surgical pattern, they were divided into two groups: the total thoracoscopic surgery group (36 patients, 27 females, aged 29 ± 9.52 years), and a mini-sternotomy group (31 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…The study included 36 patients aged 29 ± 9.52 years, the results revealed that the time of artificial circulation was 112 ± 23.16 minutes and the time of aortic clamping was 65 ± 19.94 minutes, the time of postoperative hospital stay was 5.11 ± 2 .48 days, according to drainages 139.86 ± 111.71 ml. Compared to the data in our study group, there is a higher age, longer bypass time and longer aortic cross-clamping time than in our study 14 .…”
Section: Discussioncontrasting
confidence: 96%
“…The study included 36 patients aged 29 ± 9.52 years, the results revealed that the time of artificial circulation was 112 ± 23.16 minutes and the time of aortic clamping was 65 ± 19.94 minutes, the time of postoperative hospital stay was 5.11 ± 2 .48 days, according to drainages 139.86 ± 111.71 ml. Compared to the data in our study group, there is a higher age, longer bypass time and longer aortic cross-clamping time than in our study 14 .…”
Section: Discussioncontrasting
confidence: 96%
“…In addition, the incidence of SVA is higher in young to middle-aged adults; the total thoracoscopic approach has a better chance of reoperation than median sternotomy. The total thoracoscopic technique has been reported and effectively used for some congenital cardiac diseases, such as VSD and atrial septal defect (19,20). Fukumoto et al (21) reported a case of aorto-right ventricular fistula using 3D endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding totally endoscopic aortic valve replacement (TEAVR), previous studies have indicated that it is a safe and feasible alternative to perform AVR [3][4][5][6]. In the field of ventricular septal defect repair, a comparison between totally endoscopic and Mini-sternotomy-AVR (Mini-AVR) showed that outcomes were similar in both groups [7]. However, to our knowledge, no studies compared the clinical outcomes after TEAVR to Mini-AVR.…”
Section: Introductionmentioning
confidence: 99%